Balancing stakeholder interests and paradoxes in health data sharing within health ecosystems - Wang, Fan; Mohamed, Mahmoud; Ahokangas, Petri; Karppinen, Pasi (Finnish Journal of eHealth and eWelfare, 2024)
Personal health data sharing can facilitate value co-creation between multiple stakeholders, including individuals, public organisations, private companies, research institutes, and policymakers. Yet, when companies are involved in sharing health data to develop health-related solutions, it can lead to conflicts and contradictions between stakeholders. We apply a qualitative research approach over two cases in the Finnish healthcare sector to explore the tensions and contradictions in sharing personal health data that companies can utilise in the development of new products/or services in the healthcare sector. We identify the tensions and paradoxes from multiple stakeholders’ perspectives and provide management approaches on three levels: (I) The micro-level focusing on individuals as users, (II) The meso-level concerns businesses operating within the digital health ecosystem. (III) The macro-level addresses broader societal impact and policies governing the secondary use of health data.